(untitled) (Research, Society and Development, 2023)
Introduction: Atypical hemolytic uremic syndrome (aHUS) is a rare condition of thrombotic microangiopathy, with multisystem involvement and is clinically manifested by the triad of non-immune microangiopathic hemolytic anemia, thrombocytopenia and renal injury. The prognosis in these cases is unfavorable due to the high rate of morbidity and mortality in the acute phase, in addition to the risk of progression to end-stage chronic kidney disease in around 50% of cases. The objective of this work is to report the case of a pediatric patient with the development of chronic kidney disease (CKD)., demonstrating the importance of early diagnosis, in addition to longitudinal monitoring for adequate management of comorbidities. Clinical case: Student, 9 years old, female, diagnosed with atypical hemolytic-uremic syndrome 5 years ago and undergoing irregular outpatient follow-up with pediatric nephrology since then. During this period, he presented a gradual deterioration in renal function, developing CKD and currently, he presents associated complications, such as anemia, short stature and hypertension. Discussion: As stated, one of the consequences of aHUS is the progression to CKD.